Improving Flexural Behavior of Textile Reinforced Concrete One Way Slab by Removing Weft Yarns with Different Percentages - Omar Hamid Hussien; Amer M. Ibrahim; Suhad M. Abd (Salehan Institute of Higher Education, 2018)
Textile reinforced concrete that developed at recent years is composed of the continuous textile fabric incorporated into the cementitious matrix. The geometry of the textile reinforcements has a great influence on the TRC overall behavior since it affects the bond efficiency perfectly. The effect of weft yarns removing on the flexural behavior of (1500 × 500 × 50) mm one way slabs was investigated, eight layers of the carbon fabric were used with (50%, 67% and 75%) removing of weft yarns in addition to one specimen without removing. The four one- way slabs were casted by hand lay-up method, cured for (28) days and tested in flexure using four points method. The bending capacity and the bond efficiency factor were calculated according to the conditions of the equilibrium models by comparing with experimental results. The results revealed that with higher removing proportion there was a perfect improvement in the flexural capacity, higher first crack load, eminent post cracking stiffness, higher average concrete strain and lower ultimate mid span deflection and higher toughness and ductility. Furthermore, the results clarified that there is an optimum percent of weft yarns removing at which the damage occurrence around the weft yarns is significantly reduced, and this negative effect constriction overcome the positive anchoring effect.